Pengaruh Self actualization Need dan Reward terhadap Kinerja Pegawai Pada Kantor Dinas Sosial Provinsi Gorontalo - Sulaiman, Sulaiman; Rahmisyari, Rahmisyari (Hulondalo Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2024)
This research aims to evaluate the extent to which Self Actualization Need (X1) and Reward (X2) jointly influence employee performance (Y) at the Gorontalo Province Social Service Office. This research uses a quantitative approach involving sampling from 97 employees. The data used is primary data collected through distributing questionnaires to employees. Data analysis was carried out using the path analysis method with the help of SPSS software. The research results show that Self Actualization Need (X1) and Reward (X2) together influence employee performance (Y) at the Gorontalo Provincial Social Service Office by 0.646 (64.6%), while the remainder is influenced by other variables by 0.354 (35 .4%). The need for self-actualization (X1) has an effect of 0.438 (43.8%), while appreciation (X2) has a partial effect of 0.399 (39.9%) on Employee Performance (Y).